Block universe in the context of the new spacetime substantivalism - Luty, Damian (Hybris, 2015)
The goal of the paper is to present the problem of time, which emerges in the context of the discussion about the ontological status of spacetime. The problem is a consequence of the progress of the participants of the discussion due to the application of the hole argument to the dispute. I present the shortened history of the hole argument, characterize the participants of the mentioned dispute, their development, I give a formulation of the timeless ontology and the attempts to negate it by the new spacetime substantivalists. I present and discuss a thesis suggesting that those attempts are futile.